PENYELESAIAN DELIK PERZINAHAN MENURUT ADAT MELAYU DI KAMPUNG MELAYU KOTA BENGKULU - Reza Tri Mahendra; Muhammad Ilham Adi Nugroho; Gilberto Ingot Manuel Simaremare; Akbar Hidayat Fu Aditya; Ria Anggraeni Utami (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
Bengkulu Province still holds fast to its customs and is rich in ethnic groups. With the diversity of ethnic groups, the author is interested in researching one of the ethnic groups in Bengkulu Province, namely the Malay ethnic group, especially the Malay ethnic group who live or reside in Bengkulu City. Bengkulu City has four types of customs, but this study only focuses on Malay Customs related to violations related to adultery in Malay customs that apply in Bengkulu City. Bengkulu City consists of 9 (nine) sub-districts and 67 villages, but in this study it is limited to only occupying the Kampung Melayu area. The purpose of this study is to determine and describe the resolution of customary violations related to adultery according to the Malay customs of Bengkulu City and to determine and describe the form of sanctions for customary violations related to morality according to the Malay customs of Bengkulu City. The research method used in this study uses empirical legal research and an empirical legal approach, namely a non-doctrinal approach. The results of the study on the resolution of customary violations related to adultery in the Malay customs of Bengkulu City are reports from residents, reports to the village head, summons or notification of customary officials, customary hearings, decisions of deliberations at the customary council, and implementation of customary ceremonies. The form of sanctions for customary violations related to adultery according to the Malay customs of Bengkulu City is that the perpetrator of the customary violation apologizes to the victim, the victim's family and the community for the actions he has committed, makes a letter of agreement aimed at preventing the perpetrator from repeating his actions again and gives a warning to others so that the same violation does not occur, pays customary fines, cleans the village, marries, and is expelled or exiled to another area. The conclusion and suggestion in this study is that the Bengkulu City Regional Government is expected to immediately establish regional regulations on customs, and each village is expected to make customary regulations or customary village regulations for their respective village areas.Provinsi Bengkulu masih memegang teguh adat istiadatnya dan kaya akan suku bangsa. Dengan keberagaman suku bangsa tersebut, penulis tertarik untuk meneliti salah satu suku bangsa di Provinsi Bengkulu yaitu suku bangsa Melayu, khususnya suku bangsa Melayu yang bermukim atau berdomisili di Kota Bengkulu. Kota Bengkulu memiliki empat jenis adat istiadat, namun dalam penelitian ini hanya difokuskan pada Adat Melayu terkait pelanggaran terkait perzinaahan dalam adat Melayu yang berlaku di Kota Bengkulu. Kota Bengkulu terdiri dari 9 (sembilan) kecamatan dan 67 kelurahan, namun dalam penelitian ini dibatasi hanya mengambil pada wilayah Kampung Melayu. Tujuan penelitian ini adalah untuk mengetahui dan mendeskripsikan penyelesaian pelanggaran adat yang berkaitan dengan perzinahan menurut adat Melayu Kota Bengkulu dan untuk mengetahui dan mendeskripsikan bentuk sanksi pelanggaran adat yang berkaitan dengan perzinahan menurut adat Melayu Kota Bengkulu. Metode penelitian yang digunakan dalam penelitian ini menggunakan penelitian hukum empiris dan pendekatan hukum empiris yaitu pendekatan nondoktrinal. Hasil penelitian mengenai penyelesaian pelanggaran adat yang berkaitan dengan perzinahan adat Melayu Kota Bengkulu adalah laporan dari warga, laporan kepada kepala desa, pemanggilan atau pemberitahuan pejabat adat, sidang adat, keputusan musyawarah pada dewan adat, dan pelaksanaan upacara adat. Bentuk sanksi pelanggaran adat yang berkaitan dengan pezinahan menurut adat Melayu Kota Bengkulu yaitu, pelaku pelanggaran adat meminta maaf kepada korban, keluarga korban dan masyarakat atas perbuatan yang telah dilakukannya, membuat surat perjanjian yang bertujuan agar pelaku tidak mengulangi perbuatannya lagi dan memberikan teguran kepada orang lain agar tidak terjadi pelanggaran yang sama, membayar denda adat, cuci kampung, menikahkan, dan diusir atau dibuang ke daerah lain. Kesimpulan dan saran dalam penelitian ini yaitu Pemerintah Daerah Kota Bengkulu diharapkan segera menetapkan peraturan daerah tentang adat, serta masing-masing desa diharapkan membuat peraturan adat atau perdes adat untuk wilayah desanya masing-masing.